2015
DOI: 10.3171/2015.3.spine1598
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo leaf sign: a highly predictive imaging feature of spinal meningioma

Abstract: OBJECT Spinal meningioma and schwannoma are the most common spinal intradural extramedullary tumors, and the differentiation of these 2 tumors by CT and MRI has been a matter of debate. The purpose of this article is to present a case series of spinal meningiomas showing unique imaging features: a combination of a fan-shaped spinal cord and a streak in the tumor. The authors termed the former imaging feature “ginkgo leaf sign” and evaluated its diagnostic value. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…By contrast, schwannomas generally originate from the dorsal rootlets and are usually found in the dorsal or dorsolateral side to the spinal cord. 13) In the present case, T2-weighted MR images depicted the extradural part as mixed signal intensity and the intradural component as low signal intensity. Retrospectively, these differences in the signal intensity suggested that the extra- and intradural components had discrete histology.…”
Section: Discussionsupporting
confidence: 46%
“…By contrast, schwannomas generally originate from the dorsal rootlets and are usually found in the dorsal or dorsolateral side to the spinal cord. 13) In the present case, T2-weighted MR images depicted the extradural part as mixed signal intensity and the intradural component as low signal intensity. Retrospectively, these differences in the signal intensity suggested that the extra- and intradural components had discrete histology.…”
Section: Discussionsupporting
confidence: 46%
“…[15,17] There are some diagnostic features for typical meningioma that can facilitate the diagnosis of spinal meningiomas on MRI; they are well-circumscribed lesions which have broad-based dural attachment, dural tail sign (60%-70%), and ginkgo leaf sign in meningiomas arising lateral or ventrolateral to the medulla spinalis. [15,20] Occasionally, densely calcified spinal meningiomas are hypointense on T1WI and T2WI sequences, as well as calcified spinal meningiomas show only minimal contrast enhancement. [15,18] We did not have calcified spinal meningiomas in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Yamaguchi et al (23) reported a specific MRI feature related to fan-shaped deformity of the spinal cord from a spinal meningioma along its lateral or ventrolateral margin. The deformity is created by tethering of the tumor to the dura and a stretched dentate ligament.…”
Section: Meningiomamentioning
confidence: 99%